Antigenic analysis of the major outer membrane protein of Haemophilus somnus with monoclonal antibodies. - Tagawa, Y (1993)
The major outer membrane protein of Haemophilus somnus possesses at least five distinct epitopes. Three surface-exposed epitopes on the major outer membrane protein include a conserved epitope with potential for development of a vaccine and a diagnostic test and two variable epitopes responsible for antigenic differences among strains; the remaining two epitopes are well preserved among strains but not exposed on the cell surface.